2021
DOI: 10.3390/jintelligence9010007
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Underpinnings of Multiply-Constrained Problem Solving

Abstract: Individuals encounter problems daily wherein varying numbers of constraints require delimitation of memory to target goal-satisfying information. Multiply-constrained problems, such as the compound remote associates, are commonly used to study this type of problem solving. Since their development, multiply-constrained problems have been theoretically and empirically related to creative thinking, analytical problem solving, insight problem solving, and a multitude of other cognitive abilities. In the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Self-management indicators, mostly assessed with self-assessment type questionnaires, are also related to academic achievement ( Pintrich et al 1993 ; Zimmerman and Martinez-Pons 1988 ; Abd-El-Fattah 2010 ; Veenman et al 2014 ). Problem-solving skills (assessed via various methodological approaches) and cognitive ability also show interrelationships (e.g., Chuderski and Jastrzębski 2018 ; Kretzschmar et al 2017 ; Ellis et al 2021 ). In general, these results indicate that there is a set of cognitive abilities and additional skills which together can predict a student’s learning performance in regular learning settings.…”
Section: Introductionmentioning
confidence: 99%
“…Self-management indicators, mostly assessed with self-assessment type questionnaires, are also related to academic achievement ( Pintrich et al 1993 ; Zimmerman and Martinez-Pons 1988 ; Abd-El-Fattah 2010 ; Veenman et al 2014 ). Problem-solving skills (assessed via various methodological approaches) and cognitive ability also show interrelationships (e.g., Chuderski and Jastrzębski 2018 ; Kretzschmar et al 2017 ; Ellis et al 2021 ). In general, these results indicate that there is a set of cognitive abilities and additional skills which together can predict a student’s learning performance in regular learning settings.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of this study is that it was conducted with a time limit of 7 min. It is common to perform Raven matrices with a time limit, even with a stricter time limit than our current study (e.g., 18 items with a 10-min time limit: Ellis et al, 2021 ; Robison & Campbell, 2023 ; Tsukahara & Engle, 2021 ). Based on an overview of studies in the Supplementary Material, there seem to be some indications that if no time limit is used (as the Raven matrices are supposed to be administered), response time is more determined by item difficulty.…”
Section: Discussionmentioning
confidence: 95%
“…The current study used a short 12-item version of the RAPM. However, the edge density can also be computed for the remaining items and then correlated with the response times observed for those items in the literature (for studies that provide response times per RAPM item, see Adam & Vogel, 2018 ; Ellis et al, 2021 ; Frischkorn & Von Bastian, 2021 ; Goldhammer et al, 2015 ; Gonthier & Roulin, 2020 ; Liu et al, 2022 ; Loesche et al, 2015 ; Poulton et al, 2022 ; Rivollier et al, 2021 ; Robison & Campbell, 2023 ; Sense et al, 2019 ; Tsukahara & Engle, 2021 , 2023 ; and Vigneau et al, 2006 ). If using this approach, the edge density correlated between 0.27 and 0.73 with the mean response time, and Raven item number (1 to 36) correlated between 0.51 and 0.87 with the mean response time (see Supplementary Material ).…”
Section: Resultsmentioning
confidence: 99%
“…A study showed that students who had higher self-assessed problem-solving skills reported having less stress about their ability to deal with distance learning (Hacatrjana, 2021a). There is a variety of approaches to studying problem-solving, and based on various methodological and theoretical approaches, problem-solving skills are significantly related to academic outcomes and cognitive abilities, studied with tests or questionnaires (e.g., Ellis et al, 2021;Fitzpatrick et al, 2020;Greiff et al, 2013;Kretzschmar et al, 2017). Definitions of problem-solving vary but most researchers agree that there are several processes that occur during the solving of the problem, such as exploring and understanding, representing and formulating, planning and executing, and monitoring and reflecting (OECD, 2013).…”
Section: Relation Between Academic Achievement and Other Variablesmentioning
confidence: 99%